2002
DOI: 10.1177/107110070202300909
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Strain Measurement With Determination of a Zero Strain Reference for the Medial and Lateral Ligaments of the Ankle

Abstract: The strain changes of the central part of the anterior talofibular ligament (ATFL), the posterior talofibular ligament (PTFL), the calcaneofibular ligament (CFL), and the tibiocalcaneal ligament (TCL) were measured simultaneously for a full range of ankle motion. Twelve fresh frozen amputated ankles were used. To measure the strain changes of the ligaments, a Galium-Indium-filled silastic strain transducer was implanted in the center of each ligament. The zero strain reference was determined immediately after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 11 publications
4
57
1
Order By: Relevance
“…A cadaver study by Ozeki et al (2002) shows that maximum strains in the ATaFL, PTaFL, CaFL, and ATiFL for a physiological range of ankle motion are 7.9%, 5.9%, 5.3%, and 5.2%, respectively. Similarly Colville et al (1990), using cadavers with 201 of dorsiflexion, document ankle ligament strains of approximately 4%, 6% and 8% in the ATaFL, ATiFL and PTiFL, respectively, which have been recently simulated by Wei et al (2011) using the current computational model.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…A cadaver study by Ozeki et al (2002) shows that maximum strains in the ATaFL, PTaFL, CaFL, and ATiFL for a physiological range of ankle motion are 7.9%, 5.9%, 5.3%, and 5.2%, respectively. Similarly Colville et al (1990), using cadavers with 201 of dorsiflexion, document ankle ligament strains of approximately 4%, 6% and 8% in the ATaFL, ATiFL and PTiFL, respectively, which have been recently simulated by Wei et al (2011) using the current computational model.…”
Section: Tablementioning
confidence: 99%
“…Approximately 80% of ankle sprains are lateral ankle sprains caused by excessive inversion (Fong et al, 2009) while high ankle sprains comprise about 10% (Boytim et al, 1991). Some studies have examined ankle ligament strains using cadavers (Colville et al, 1990;Ozeki et al, 2002;Tochigi et al, 2005). Using a combined dual-orthogonal fluoroscopic and magnetic resonance imaging (MRI) technique, De Asla et al (2009) measure in vivo changes in length of the anterior talofibular ligament (ATaFL) and calcaneofibular ligament (CaFL) in four static foot positions.…”
Section: Introductionmentioning
confidence: 99%
“…Data based on the published literature [14,16,[30][31][32] and passive torque collected from participants were used for model validation. The lengths of ankle ligaments depend on not only the bone geometry, but also their origin and insertion points on bones.…”
Section: Model Validationmentioning
confidence: 99%
“…Ankle assessment at the level of muscles and ligaments usually consists of cadaver-based sectioning studies [13,14], invasive techniques [15] and image-based methods [16]. Cadaver-based and invasive methods are not suitable for rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In-vivo strain of ligament is often measured by differential variable reluctance transducer (DVRT), liquid mercury strain gauge, and Hall-effect strain transducers (Woo et al, 1999). Studies of in-vivo strain of ankle ligaments with cadaver ankles revealed that ATFL is elongated in plantarflexion and shortened in dorsiflesion, but the reverse is found in calcaneofibular ligament (CFL) and posterior talofibular ligament (PTFL) (Ozeki et al, 2002). Butler and Walsh (2004) added that every ligament at lateral ankle does relax when the loaded is less than 5N, however, the ATFL does not relax to same extent as the other ligaments.…”
Section: Establishing Aetiology and Mechanismmentioning
confidence: 99%